2016
DOI: 10.1111/ppl.12470
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of transcription factors involved in maize embryonic callus formation

Abstract: In this study, a maize inbred line with a strong capacity to induce embryonic callus, 18-599R, was used to analyze the transcription factors expressed during embryonic callus formation. A total of 1180 transcription factors were found to be expressed during three key stages of callus induction. Of these, compared with control, 361, 346 and 328 transcription factors were significantly downregulated during stages I, II and III, respectively. In contrast, 355, 372 and 401 transcription factors (TFs) were upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
0
27
1
Order By: Relevance
“…Among them, the bZIP (51 members), GRAS (30 members), MADS-box (22 members), K-box (22 members), TCP (12 members), and SBP-box (11 members) families were the largest involved in Pb stress ( Figure 2 A). Compared with a previous finding that approximately 62.9% of TFs in immature maize embryos respond to exogenous 2, 4-D, and that MYB and BHLH are the largest families of DETs [ 19 ], our current research revealed that a smaller proportion of TFs and a different composition of TF families in maize roots participated in the response to Pb stress.…”
Section: Resultscontrasting
confidence: 82%
“…Among them, the bZIP (51 members), GRAS (30 members), MADS-box (22 members), K-box (22 members), TCP (12 members), and SBP-box (11 members) families were the largest involved in Pb stress ( Figure 2 A). Compared with a previous finding that approximately 62.9% of TFs in immature maize embryos respond to exogenous 2, 4-D, and that MYB and BHLH are the largest families of DETs [ 19 ], our current research revealed that a smaller proportion of TFs and a different composition of TF families in maize roots participated in the response to Pb stress.…”
Section: Resultscontrasting
confidence: 82%
“…Furthermore, eight quantitative trait loci (QTL) and three epistatic interactions were found to control type I callus formation in a maize recombinant inbred line (RIL) population (Krakowsky et al, 2006 ). In previous studies, some transcription factors and microRNAs in hormone signal transduction pathways were found to regulate the process of embryonic callus induction (Shen et al, 2013 ; Ge et al, 2016 ). To date, research exploring callus regenerative capacity has mainly focused on Arabidops is, rice, wheat, maize, and other plants.…”
Section: Introductionmentioning
confidence: 98%
“…As one of the main crops for animals and humans, maize ( Zea mays L.) is an important target for genetic manipulation (Zhang et al, 2014 ; Li et al, 2016 ). However, during maize transformation, difficulty in embryonic callus induction and regeneration, which occurs in most elite lines, presents a major bottleneck (Shen et al, 2012 , 2013 ; Ge et al, 2016 ). Previous studies have suggested that both genotypes and exogenous hormones affect embryonic callus induction from maize immature embryos, such as abscisic acid (ABA), indole acetic acid (IAA), and gibberellic acid (GA3) widely considered to play important roles in callus formation (Jiménez and Bangerth, 2001 ; Ge et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, a bHLH domain consists of approximately 60 amino acids comprising a stretch of approximately 15 basic amino acids at the N-terminus, followed by two regions of hydrophobic residues predicted to form amphipathic helices separated by an intervening loop 16 . With the increasing number of completed and draft plant genomes, more than one thousand bHLH transcription factors have been identified not only in crops (soybean, potato, tomato or rice) 14 , 17 and model plants (Arabidopsis; tobacco) 16 , 18 but also in pharmaceutical plants ( Salvia miltiorrhiza ; Panax notoginseng ) 7 , 19 . Interestingly, higher plants have more bHLH transcription factors (about 150) and a larger gene family (approximately 26 subfamilies) than most animal species 12 , 20 .…”
Section: Introductionmentioning
confidence: 99%